Cambios esqueléticos cefalométricos en la base craneal post expansión rápida del maxilar - Chileno-Aquiño, Beatriz (2014)
Rapid Maxillary Expansion (ERM) has been classically described in the literature as a therapeutic procedure in the treatment of transverse maxillary deficiency. The aim of this study was to evaluate the cephalometric skeletal changes on the cranial base in growing patients who had undergone rapid maxillary expansion. The material consisted of lateral radiographs taken from ten growing patients (eight male and two female) with need of rapid maxillary expansion as part of their orthodontic treatment. The age range of the patients was 7.1 to 12.7 years, and the mean age was 10.6 ± 2.04 years. Lateral radiographs of each patient were taken before treatment (T1) and immediately after the active phase of treatment (T2). The evaluated variables were: NSBa angle, NBa/F.H. angle, SN/ENA-ENP angle, F.H./ENA-ENP angle, SN/F.H. angle, S-N distance, S-Ba distance and N-Ba distance. The data were statistically analyzed using the paired Student´s t-test (p<0.05). According to the statistical analysis, significant changes were found in all the evaluated variables. Therefore, it can be speculated that rapid maxillary expansion has had not only local skeletal effects but also significant skeletal changes on the cranial base.